COMPARISON OF ANGER LEVELS OF THE SEDENTARY WOMEN AND THE WRESTLER WOMENS - Emrah ATAY (Fırat University, 2019)
Anger is an emotional response that is born in the first years of life. Uncontrolled anger levels can be harmfull to the athlete and his or her sport. The purpose of the present research is comparing the anger levels of sedentary and wrestler women. In the present research, 109 (46.4%) sedentary and 126 (53.6%) wrestler, the total of 235 women of age 14.98±1.25 years, height 162.00±0.06 cm and weight 54.15±11.51 kg voluntarily participated. In order to collect data, “The State-Trait Anger Expression Inventory” developed by Spielberger, and adapted to Turkish by Özer was applied on the participants. Collected data were analysed through statistical methods developed for social sciences. Whether collected data distributed normally was tested with Kolmogorov-Smirnov test. Collected data were analysed with Mann-Whitney U test. Data were analysed within 95% confidence interval and 0.05 significance level. Wrestler women tested of higher anger in Trait-Anger subscale of The State-Trait Anger Expression Inventory than sedentary women. Yet, the difference wasn’t statistically significant (p>0.05). Anger-In levels of wrestler women were significantly higher than sedentary women (p